2014
DOI: 10.1186/1472-6831-14-37
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of Aggregatibacter actinomycetemcomitans and its cdtB gene in subgingival plaque of Chinese periodontitis patients

Abstract: BackgroundAggregatibacter actinomycetemcomitans (A.actinomycetemcomitans) is an important periodontal pathogen that can participate in periodontitis and other non-oral infections. The cytolethal distending toxin (Cdt) is among the virulence factors produced by this bacterium. This study was to elucidate the distribution of A.actinomycetemcomitans and the prevalence of its cdtB gene in Chinese subjects.MethodsA total of 255 subgingival samples were obtained from 30 subjects. Samples were collected from periodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
15
0
2
Order By: Relevance
“…4,19,27,[29][30][31][32][33][34][35] A total of 6,376 patients (AgP = 1,978 and CP = 4,398) and 23,920 subgingival biofilm samples were evaluated (AgP = 8,224 and CP = 15,696). The samples were analyzed individually in 26 studies 3,5,6,18,20,[23][24][25]27,29,30,32,33,44,46,57,59,71,[73][74][75][76][77]82,84,85 and pooled in 28 studies. 4,16,17,19,21,22,26,28,31,34,35,[38][39][40][41]…”
Section: Methodological Features Of the Studies Included And Demogramentioning
confidence: 99%
See 1 more Smart Citation
“…4,19,27,[29][30][31][32][33][34][35] A total of 6,376 patients (AgP = 1,978 and CP = 4,398) and 23,920 subgingival biofilm samples were evaluated (AgP = 8,224 and CP = 15,696). The samples were analyzed individually in 26 studies 3,5,6,18,20,[23][24][25]27,29,30,32,33,44,46,57,59,71,[73][74][75][76][77]82,84,85 and pooled in 28 studies. 4,16,17,19,21,22,26,28,31,34,35,[38][39][40][41]…”
Section: Methodological Features Of the Studies Included And Demogramentioning
confidence: 99%
“…Aggregatibacter actinomycetemcomitans 13 3,16,17,33,36,41,45,47,72,[77][78][79][80] 0 24 [4][5][6][18][19][20]22,24,27,29,30,32,38,39,42,46,49,57,59,73,74,76,81,82 Moderate Fusobacterium nucleatum 3 6,75,77 0 1 4 5,16,17,19,29,[33][34][35]38,43,57,73,74,79 Parvimonas micra 3 33,34,57 0 1 5 [4]…”
Section: Strongmentioning
confidence: 99%
“…A. actinomycetemcomitans is a bacteria frequently associated with periodontitis [ 54 ], and numerous studies have found that the majority of these strains harbor CDT (from 66% to 86% depending on the study) [ 50 , 54 , 55 , 56 ]. Periodontitis is an inflammatory state of the tooth-supporting structures (gingiva, alveolar bone, periodontal ligament and cementum).…”
Section: Cdt-producing Bacteria In Diseasesmentioning
confidence: 99%
“…Data from some studies have indicated a correlation between the presence of Cdt + A. actinomycetemcomitans strains and periodontal disease while other studies have failed to find a difference between colonization of subjects with disease by Cdt + and Cdt − strains. A representative collection of studies in which Cdt + and Cdt − strains of A. actinomycetemcomitans were quantified by either culturing or PCR in localized aggressive periodontitis (LAP) subjects and clinically healthy controls yielded mixed results in relation to a positive correlation between the toxin and disease [19,[191][192][193][194][195][196][197]. In one of these studies, a random cohort of 500 Ghanaian adolescents (mean age 13 years) was examined for the presence of A. actinomycetemcomitans and expression of the AaCdt at baseline and in 397 of the subjects two years later [191].…”
Section: Contribution Of the Aacdt To Oral Infectious Diseasementioning
confidence: 99%